Efficiency and productivity growth of domestic and foreign commercial banks in Malaysia - Kent Matthews; Mahadzir Ismail (Cardiff University, Cardiff Business School, 2006)
This study examines the technical efficiency and productivity of domestic and foreign commercial banks in Malaysia 1994-2000. We find that foreign banks have a higher efficiency level than domestic banks, and that efficient banks are characterised by size but not profitability or loan quality. The main source of productivity growth is technical change rather than improvement in efficiency. The productivity of domestic banks is more susceptible to macroeconomic shocks than foreign banks but over the medium term foreign banks are only marginally superior to domestic banks.
Keywords: D2; G2; 330; domestic and foreign banks; technical efficiency; Malmquist productivity index